The inner West : an introduction to the hidden wisdom of the West - Kinney, Jay, 1950- (New York : Jeremy P. Tarcher/Penguin, 2004)
Spiritual seekers have often looked to the East for inspiration and guidance. Yet increasing numbers of people are discovering that many helpful wisdom traditions have existed right here in the West. With the Kabbalah and Tarot cards more popular than ever, and alternative spirituality from Wicca to Sufism gaining a new audience, this is a timely book for this expanding audience. More than twenty essays by seventeen leading authors shine a light on some of the most mysterious and closely held aspects of the Western tradition. The authors bring to life the symbolist and occult philosophies that populate the history and beliefs of the Western way.--From publisher description.
Hermes and alchemy : the winged god and the golden word / Richard Smoley -- The star-gods of Neoplatonism / Kenneth Stein -- The quest for spiritual freedom : the Gnostic worldview / Stephan A. Hoeller -- Kabbalah and Jewish mysticism : an overview / Pinchas Giller -- The mysticism of Christian teaching / Theodore J. Nottingham -- Sufism : a path to human wholeness / Kabir Helminski -- The quest of the magus : a summary of the western magical tradition / Thomas D. Worrel -- The unexamined tarot / Chas S. Clifton -- Ladder to labyrinth : the spiritual and psychological dimensions of astrology / Priscilla Costello -- Sophia : goddess of wisdom / Caitlin Matthews -- Explaining Wicca / Judy Harrow -- The hidden sages and the Knights Templar / Robert Richardson -- The Rosicrucian dream / Christopher McIntosh -- Masonic civilization / Richard Smoley -- Heavens and hells : the inner worlds of Emanuel Swedenborg / Gary Lachman -- Blavatsky and her masters / K. Paul Johnson -- The apocalyptic Steiner / Anastasy Tousomou -- r Joscelyn Godwin.
Includes bibliographical references (p. 309-322).
Keywords: Occultism